Impact of betaine on laying hens’ productive and physiological reactions at the late stage of production - Al-khalaifah, Hanan S.; Al-Ardhi, Saad Attallah; Nafea, Husam H.; Al-Nasser, Afaf; Khalil, Hassan A.; Hassan, Mahmoud I. S.; Ahmed, Hitham A. (Frontiers in Animal Science, 2025)
IntroductionDue to the anti-inflammatory, antioxidant, and antibacterial properties of betaine, it may serve as a beneficial feed supplement for laying hens. This research aimed to evaluate whether betaine enhances the productive, reproductive, and intestinal health of layer hens.MethodsA total of 240 laying hens, aged 60 weeks, were divided into four treatment groups, each consisting of 60 hens. Each group was further divided into four replicates of 15 hens each. The first group, designated as the control (CTRL), received only the basal diet. The other treatment groups received the basal diet supplemented with betaine at levels of 0.3, 0.6, and 1.2 g/kg. The experiment was conducted over 24 weeks.ResultsThe results indicated that the addition of betaine improved the growth performance traits of Fayoumi laying hens. Specifically, the inclusion of 0.6 g of betaine per kilogram of feed led to increased fertility (p ≤ 0.05) and hatchability rates. In addition, betaine treatment significantly enhanced (p ≤ 0.05) both the absolute and relative carcass weights while reducing abdominal fat. Moreover, a betaine level of 1.2 g/kg improved the lipid profile by lowering the serum levels of total lipids, cholesterol, and low-density lipoprotein (LDL). This level also significantly (p ≤ 0.05) increased the counts of beneficial bacteria, including the total bacterial count (TBC) and Lactobacillus, in the cecum while reducing the count of pathogenic bacteria.DiscussionOverall, dietary treatments with betaine, particularly at levels of 0.6 and 1.2 g/kg, could enhance the performance, carcass traits, blood indices, and cecal bacterial populations of Fayoumi laying hens.